FUTURE-GB: functional and ultrasound-guided resection of glioblastoma – a two-stage randomised control trial. Issue 11 (15th November 2022) - Plaha, Puneet; Camp, Sophie; Cook, Jonathan; McCulloch, Peter; Voets, Natalie; Ma, Ruichong; Taphoorn, Martin J B; Dirven, Linda; Grech-Sollars, Matthew; Watts, Colin; Bulbeck, Helen; Jenkinson, Michael D; et al.
Abstract : Introduction: Surgery remains the mainstay for treatment of primary glioblastoma, followed by radiotherapy and chemotherapy. Current standard of care during surgery involves the intraoperative use of image-guidance and 5-aminolevulinic acid (5-ALA). There are multiple other surgical adjuncts available to the neuro-oncology surgeon. However, access to, and usage of these varies widely in UK practice, with limited evidence of their use. The aim of this trial is to investigate whether the addition of diffusion tensor imaging (DTI) and intraoperative ultrasound (iUS) to the standard of care surgery (intraoperative neuronavigation and 5-ALA) impacts on deterioration free survival (DFS). Methods and analysis: This is a two-stage, randomised control trial (RCT) consisting of an initial non-randomised cohort study based on the principles of the IDEAL (Idea, Development, Exploration, Assessment and Long-term follow-up) stage-IIb format, followed by a statistically powered randomised trial comparing the addition of DTI and iUS to the standard of care surgery. A total of 357 patients will be recruited for the RCT. The primary outcome is DFS, defined as the time to either 10-point deterioration in health-related quality of life scores from baseline, without subsequent reversal, progressive disease or death. Ethics and dissemination: The trial was registered in the Integrated Research Application System (Ref: 264482) and approved by a UK research and ethics committee (Ref: 20/LO/0840). Results will be published in a peer-reviewed journal. Further dissemination to participants, patient groups and the wider medical community will use a range of approaches to maximise impact. Trial registration number: ISRCTN38834571 .